ENHANCING TOURIST VISITS THROUGH DIGITAL PROMOTION IN BONGKASA PERTIWI VILLAGE - Gusti Ngurah Indra Ariestyawan; Ida Bagus Putra Yadnya; Francisca Titing Koerniawaty (CV. Lafadz Jaya, 2026)
The development of digital technology has changed the way tourist destinations are promoted, but tourist villages still face limitations in utilizing digital media. This study aims to design a digital promotion strategy to increase the popularity and tourist visits to Bongkasa Pertiwi Tourism Village, Bali. A descriptive applicative qualitative approach was used through interviews, observations, and documentation. Analysis was conducted thematically with a SWOT framework to identify supporting and inhibiting factors. The results show that digital strategies have not been optimally integrated, with the main obstacles being limited human resources, less systematic content planning, and minimal involvement of MSMEs. The strategy is designed to integrate Community-Based Tourism, the 6A concept, the AISAS model, and Cyber ​​Public Relations, with a focus on authentic content and two-way interaction. This strategy has the potential to increase visibility and encourage sustainable tourism.